Palynology of the Genus Stachytarpheta Vahl. (Verbenaceae) - Adedeji, Olubukola (2014)
The exine morphology of pollen grains of Stachytarpheta indica (Linn.) Vahl Stachytarpheta cayennensis (Rich.) Vahl and Stachytarpheta angustifolia (Mill.) Vahl is reported. This study was carried out with a light microscope. Pollen grains from fresh anthers were collected and aceolysed. Statistical analysis used to analyse the data collected include cluster analysis, correlation analysis, similarity and distance indices. The pollen grains are spheroidal to oblate to sub-oblate in shape. They are aperturate, both colpate and porate. Tricolpate types occur most frequently, acolpate, monocolpate, bicolpate and tetracolpate types less frequently. The rnulticolpate and multiporate attributes in all the species indicate that the genus is not primitive in evolutionary history and this species probably, evolved around in the same time. According to the size, the pollen grains of the genus falls into groups permagna (pollen diameter 100-200 υm) and giganta (pollen diameter greater than 200 υm). S. cayennensis and S. angustifolia belong to group perrnagna and S. indica only in the group giganta. This separates S. indica from the other two species. The large pollen grain size in the genus clearly supports the fact that the flowers in the genus are more insect-and-bird pollinated than wind pollinated. The similarity and distance indices of the species showed that S. cayennensis and S. angustifolia are the closest. S. indica is closer to S. angustifolia but farther from S. cayennensis.